Design and Evaluation of a Digital Learning Media Module Based on Alur Merdeka for Prospective Teachers - Khairun Nisa; Ely Syafitri; Elfira Rahmadani; Syarinah Junianti Hasibuan; Dewi Susanti Purba (AL-ISHLAH: Jurnal Pendidikan, 2025)
The integration of technology in education necessitates that future teachers acquire the skills to design and implement effective digital learning media. The Merdeka Curriculum, particularly through its Alur Merdeka framework, emphasizes flexible and independent learning, aligning with this need. This study aimed to develop and evaluate a Digital Learning Media module grounded in the Alur Merdeka approach to improve student competencies in educational technology. A Research and Development (RD) methodology was applied, guided by the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Module validity was assessed by expert reviewers. Practicality was gauged through student response questionnaires, and effectiveness was measured using N-Gain Scores from pretest and posttest results. The module demonstrated high validity (87.6%) and strong practicality (84%) based on expert evaluations and student feedback. Effectiveness testing showed a significant improvement in students’ competencies, with an N-Gain Score of 0.72, categorized as high. The findings confirm that the Alur Merdeka-based module is a valid, practical, and effective tool for supporting independent learning in teacher education. Its implementation can enhance prospective teachers’ ability to develop technology-driven instructional media. This study contributes to the development of flexible, competency-based digital learning resources in alignment with the Merdeka Curriculum, supporting the broader integration of technology in teacher education programs.